K‐band RF‐MEMS uniplanar reconfigurable‐bandwidth bandpass filter using multimodal immittance inverters. Issue 11 (1st May 2013) - Contreras, A.; Ribó, M.; Pradell, L.; Casals‐Terré, J.; Giacomozzi, F.; Iannacci, J.
Abstract : A K‐band RF‐MEMS uniplanar second‐order bandpass filter with reconfigurable bandwidth is presented. The filter is based on inductively‐coupled half‐wavelength slotline resonators and CPW‐slotline multimodal immittance inverters (MIIs). The coupling inductance and the MII length are reconfigured using RF‐MEMS ohmic‐contact switches. Experimental results show a 3 dB relative‐bandwidth change from 4.5 to 8.5% (maintaining a Butterworth response), and insertion losses of 5.2 and 3.7 dB for either state.